Configural Gestalts Remain Nothing More Than the Sum of Their Parts in Visual Agnosia. (December 2013) - de-Wit, Lee H.; Kubilius, Jonas; de Beeck, Hans P. Op; Wagemans, Johan
We report converging evidence that higher stages of the visual system are critically required for the whole to become more than the sum of its parts by studying patient DF with visual agnosia using a configural superiority paradigm. We demonstrate a clear dissociation between this patient and normal controls such that she could more easily report information about parts, demonstrating a striking reversal of the normal configural superiority effect. Furthermore, by comparing DF's performance to earlier neuroimaging and novel modeling work, we found a compelling consistency between her performance and representations in the early visual areas, which are spared in this patient. The reversed pattern of performance in this patient highlights that in some cases visual Gestalts do not emerge early on without processing in higher visual areas. More broadly, this study demonstrates how neuropsychological patients can be used to unmask representations maintained at early stages of processing.